2018
DOI: 10.1097/scs.0000000000004806
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric Analysis of the Dental Arches of Five-Year-Old Children With Cleft Lip and Palate

Abstract: This study aimed to analyze the dimensional alterations of the dental arches of 5-year-old children with cleft lip and palate and to compare these dimensions with children without oral clefts. One hundred twenty children were divided into the following groups: unilateral cleft lip (UCL), unilateral cleft lip and palate (UCLP), cleft palate (CP), and control (C). A specific software was used to digitize the dental casts and perform the anthropometric analyses through the measurement of transversal linear interc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 34 publications
1
23
0
1
Order By: Relevance
“…The following linear measurements were analysed: C–C′ (Intercanine distance)—transversal line between the eruption points of the primary canine; T–T′ (Intertuberosity distance)—transversal line between the left and right tuberosity; I–C′ (Left anterior intersegment length)—from the interincisive point to the eruption point of the left primary canine; I–C (Right anterior intersegment length)—from the interincisive point to the eruption point of the right primary canine; I–T′ (Left anteroposterior intersegment length)—from the interincisive point to the left tuberosity; I–T (Right anteroposterior intersegment length) from the interincisive point to the right tuberosity 1‐5,16,17 . The volume of the palatal bone shelves was analysed according to the methodology of the study of Pucciarelli et al, 2015, 18 whereas the area of the palatal bone shelves was evaluated according to Carrara et al, 2016 1 and Ambrosio et al, 2018 2 (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The following linear measurements were analysed: C–C′ (Intercanine distance)—transversal line between the eruption points of the primary canine; T–T′ (Intertuberosity distance)—transversal line between the left and right tuberosity; I–C′ (Left anterior intersegment length)—from the interincisive point to the eruption point of the left primary canine; I–C (Right anterior intersegment length)—from the interincisive point to the eruption point of the right primary canine; I–T′ (Left anteroposterior intersegment length)—from the interincisive point to the left tuberosity; I–T (Right anteroposterior intersegment length) from the interincisive point to the right tuberosity 1‐5,16,17 . The volume of the palatal bone shelves was analysed according to the methodology of the study of Pucciarelli et al, 2015, 18 whereas the area of the palatal bone shelves was evaluated according to Carrara et al, 2016 1 and Ambrosio et al, 2018 2 (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…The volume of the palatal bone shelves was analysed according to the methodology of the study of Pucciarelli et al, 2015, 18 whereas the area of the palatal bone shelves was evaluated according to Carrara et al, 2016 1 and Ambrosio et al, 2018 2 (Figure 1). One trained and calibrated examiner performed all morphometric analyses 1‐3,5,16,17 . To enable intra‐ and intergroup comparisons, bone segment volume values were added in the BCLP group 2 …”
Section: Methodsmentioning
confidence: 99%
“…The findings of this study suggesting that clefts affecting the palate (UCLP, BCLP, CP) have smaller dimensions than clefts affecting only the lip are supported by previous studies. A Brazilian study examined the transversal dimensions of the maxillas of 5-year-old cleft children and concluded that clefts affecting the palate have more maxillary dimensional alterations than those without cleft palate [ 11 ]. A study among 6-year-old patients with clefts [ 13 ] and another one among 3-year-olds [ 5 ] both reported that BCLP have the narrowest maxillary dimensions and CL has the widest.…”
Section: Discussionmentioning
confidence: 99%
“…The scar tissue formed after the repair of the cleft is thought to affect the growth of the maxilla [ 9 , 10 ]. Maxillary arch dimensions have previously been suggested to be smaller in unilateral cleft lip and palate (UCLP) and bilateral cleft lip and palate (BCLP) patients compared with cleft lip (CL) [ 11 ] and cleft palate (CP) patients [ 5 , 12 , 13 ], but contrary results suggest similar dimensions in UCLP and CP patients [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…FUDALEJ et al, 2015;JORGE et al, 2016;MIKOYA et al, 2015). No protocolo 1, na primeira fase das cirurgias primárias, aos 3 meses, foi realizada a queiloplastia pela Técnica de Millard e na segunda fase, aos 12 meses, foi executada a palatoplastia total pela ROUSSEAU et al, 2013;CARRARA et al, 2016;CÉRON-ZAPATA et al, 2016;DE MENEZES et al, 2016;FALZONI et al, 2016;HOFFMANNOVA et al, 2016;JORGE et al, 2016;AMBROSIO et al, 2018;BRUGGINK et al, 2019), entretanto, no presente estudo a idade de alguns pacientes em cada fase de tratamento excedem o previsto no protocolo da Instituição devido a questões de abordagem pré-cirurgica, saúde geral, localidade e condição socioeconômica.…”
Section: Variáveisunclassified